Self-esteem, satisfaction with life and living conditions in teenagers of fifth grade of high school: A factorial study by poverty and gender - Tarazona, David (2005)
The purpose of the present study was to explore the differences in self-esteem, satisfaction with life and habitability conditions in fifth year high school teenager students based in a factorial study by poverty and sex. Poverty was appraised by school type, because there are big breaches between poor and no-poor population in the district selected (La Molina). An anonymously and voluntarily self-reported questionnaire was used. The results shows that (1) about self-esteem, public school women had the smaller level, private school men had the highest and public school men and private school women were in a similar intermediate level; (2) about satisfaction with life, private school men had, again, the highest level, private school women had the second position and public school women and men had the smallest level with similar scores; finally (3) habitability conditions were better in private students and worst in public school students, this find reinforce the use of school type as a poverty indicator.